2020
DOI: 10.2174/1874434602014010190
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Burnout, its Associated Factors and its Effect on the Quality of Life of Critical Care Nurses Working in Buraydah Central Hospital at Qassim Region, Saudi Arabia

Abstract: Background: Burnout is a grave problem for critical care workers because they are exposed to prolonged psychosocial stressors, including advanced technology, high responsibilities and great patient acuity. The aim of this study was to investigate burnout, its associated factors and its effect on self-care among critical care nurses. Methods: A descriptive correlational research design was carried out with 170 critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 44 publications
1
23
0
7
Order By: Relevance
“…Another study by Azari and Rasouyar (2016) described QOL as a multidimensional and multifaceted concept characterized by objective and subjective features and helps finally to assess human well‐being (Azari & Rasouyar, 2016). On the other hand, six studies have adopted the definition of the WHO (Abraham & D’silva, 2013; Alotni & Elgazzar, 2020; Hatamipour et al., 2017; Kelleci et al., 2011; Kupcewicz & Jóźwik, 2020; Ribeiro et al., 2021). Last, some studies examined work‐related or professional QOL, not general QOL (Abdel‐Aziz & Adam, 2020; Casida et al., 2019; Erkorkmaz et al., 2018; Kim et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study by Azari and Rasouyar (2016) described QOL as a multidimensional and multifaceted concept characterized by objective and subjective features and helps finally to assess human well‐being (Azari & Rasouyar, 2016). On the other hand, six studies have adopted the definition of the WHO (Abraham & D’silva, 2013; Alotni & Elgazzar, 2020; Hatamipour et al., 2017; Kelleci et al., 2011; Kupcewicz & Jóźwik, 2020; Ribeiro et al., 2021). Last, some studies examined work‐related or professional QOL, not general QOL (Abdel‐Aziz & Adam, 2020; Casida et al., 2019; Erkorkmaz et al., 2018; Kim et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies ( n = 16) found a negative correlation between nurses’ burnout and their QOL or professional QOL (Abdel‐Aziz & Adam, 2020; Abraham & D’silva, 2013; Alotni & Elgazzar, 2020; Aytekin et al., 2013; Casida et al., 2019; Erkorkmaz et al., 2018; Fradelos et al., 2014; Hatamipour et al., 2017; Kelleci et al., 2011; Khatatbeh et al., 2020; Kim et al., 2019; Kupcewicz & Jóźwik, 2020; Permarupan et al., 2020; Ribeiro et al., 2021; Wang et al., 2019; Zeng et al., 2020). For example, nurses’ QOL was negatively correlated with emotional exhaustion and depersonalization, and positively with personal accomplishment (Kelleci et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was expected that critical care nurses would score lower for CS and higher for BO and STS, as mentioned by other studies. 15,31,32 In the current study, unexpectedly, nurses working at inpatient units reported high levels of CS and moderate levels of BO; high mean scores for BO and STS were observed among the same group. This may be due to the continuous routine work of inpatient nurses and the continued exposure to chronically ill patients.…”
Section: Discussionmentioning
confidence: 39%
“…The questionnaire consisted of three sets of 10 items that reflected specific measures on the ProQOL subscales: CS, BO, and STS. The total score of each subscale was interpreted as either high (≥41), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), or low (≤22). 9 In this study, the researcher evaluated the Arabic version of the ProQOL questionnaire for internal consistency using Cronbach's alpha among a sample of 334 Saudi nurses.…”
Section: Dovepressmentioning
confidence: 99%